Modified Glasgow Prognostic Score associated with survival in metastatic renal cell carcinoma treated with immune checkpoint inhibitors. Issue 7 (29th July 2021) - Brown, Jacqueline T; Liu, Yuan; Shabto, Julie M; Martini, Dylan; Ravindranathan, Deepak; Hitron, Emilie Elise; Russler, Greta Anne; Caulfield, Sarah; Yantorni, Lauren; Joshi, Shreyas Subhash; Kissick, Haydn; Ogan, Kenneth; et al.
Abstract : Background: The modified Glasgow Prognostic Score (mGPS) is a composite biomarker that uses albumin and C reactive protein (CRP). There are multiple immune checkpoint inhibitor (ICI)-based combinations approved for metastatic renal cell carcinoma (mRCC). We investigated the ability of mGPS to predict outcomes in patients with mRCC receiving ICI. Methods: We retrospectively reviewed patients with mRCC treated with ICI as monotherapy or in combination at Winship Cancer Institute between 2015 and 2020. Overall survival (OS) and progression-free survival (PFS) were measured from the start date of ICI until death or clinical/radiographical progression, respectively. The baseline mGPS was defined as a summary score based on pre-ICI values with one point given for CRP>10 mg/L and/or albumin<3.5 g/dL, resulting in possible scores of 0, 1 and 2. If only albumin was low with a normal CRP, no points were awarded. Univariate analysis (UVA) and multivariate analysis (MVA) were carried out using Cox proportional hazard model. Outcomes were also assessed by Kaplan-Meier analysis. Results: 156 patients were included with a median follow-up 24.2 months. The median age was 64 years and 78% had clear cell histology. Baseline mGPS was 0 in 36%, 1 in 40% and 2 in 24% of patients. In UVA, a baseline mGPS of 2 was associated with shorter OS (HR 4.29, 95% CI 2.24 to 8.24, p<0.001) and PFS (HR 1.90, 95% CI 1.20 to 3.01, p=0.006) relative to a score of 0; this disparity in outcome based on baseline mGPS persisted in MVA. The respective median OS of patients with baseline mGPS of 0, 1 and 2 was 44.5 (95% CI 27.3 to not evaluable), 15.3 (95% CI 11.0 to 24.2) and 10 (95% CI 4.6 to 17.5) months (p<0.0001). The median PFS of these three cohorts was 6.7 (95% CI 3.6 to 13.1), 4.2 (95% CI 2.9 to 6.2) and 2.6 (95% CI 2.0 to 5.6), respectively (p=0.0216). The discrimination power of baseline mGPS to predict survival outcomes was comparable to the IMDC risk score based on Uno's c-statistic (OS: 0.6312 vs 0.6102, PFS: 0.5752 vs 0.5533). Conclusion: The mGPS is prognostic in this cohort of patients with mRCC treated with ICI as monotherapy or in combination. These results warrant external and prospective validation.